O DESENVOLVIMENTO SUSTENTÁVEL NAS ESCOLAS E NA FORMAÇÃO DOCENTE - Scheid, Rafaela Rossana; Schmitz, Jéssica Caroline; Fröhlich, Aléxia Birck; Puhl, Mário José (Salão do Conhecimento, 2018)
Projeto de Iniciação Científica